Complementary Genomic Screens Identify SERCA as a Therapeutic Target in NOTCH1 Mutated Cancer - Roti, Giovanni (2013)
Notch1 is a rational therapeutic target in several human cancers, but as a transcriptional regulator, it poses a drug discovery challenge. To identify Notch1 modulators, we performed two cell-based, high-throughput screens for small-molecule inhibitors and cDNA enhancers of a NOTCH1 allele bearing a leukemia-associated mutation. SERCA calcium channels emerged at the intersection of these complementary screens. SERCA inhibition preferentially impairs the maturation and activity of mutated Notch1 receptors and induces a G(0)/G(1) arrest in NOTCH1-mutated human leukemia cells. A small-molecule SERCA inhibitor has on-target activity in two mouse models of human leukemia and interferes with Notch signaling in Drosophila. These studies “credential” SERCA as a therapeutic target in cancers associated with NOTCH1 mutations.